Low-load blood flow restriction training and heavy slow resistance training improve clinical outcomes equally in males with unilateral patellar tendinopathy - A randomized controlled trial - Hjortshøj, M. H.; Juneja, H.; Svensson, R. B.; Larsen, F. K.; Lundgaard-Nielsen, M.; Herzog, R. B.; Petersen, J.; Kjær, M.; Aagaard, P.; Magnusson, S. P.; Couppé, C. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Patellar tendinopathy (PT) is a debilitating overuse injury that is particularly prevalent in `jumping sports` such as e.g., volleyball and basketball. PT is also one of the primary causes of reduced physical activity, which may contribute to reduced quality of life and lifestyle diseases. The current best treatment is heavy slow resistance training (HSRT); however, not all patients can cope with heavy exercise loads. Even with HSRT, the time to improve clinically from tendinopathy might be as long as 3-12 months. The use of low-load resistance training in combination with blood flow restriction (LL-BFRT) has been advocated as a clinically relevant rehabilitation tool since it does not require the large joint and tissue forces and because it might accelerate recovery. In this RCT, we investigated the rehabilitative effect of LL-BFRT compared with HSRT at 3, 6, 12 (primary endpoint) and 52 weeks (data still being collected) in males with chronic (> 3 months) unilateral patellar tendinopathy.